No cultivo da filosofia: uma colheita interdisciplinar nos subterrâneos da rede estadual - Rodrigues, Rodrigo Mendes (2013)
This paperwork aims at promoting a collective space for philosophical conversations with the purpose of reducing the conflicts as well as the physical and symbolic violence present in the underground contexts of a State School located in the countryside of São Paulo State. The interdisciplinary principles based on Fazenda and that of biophilia based on Capra are the main theoretical references. The activities developed in this work aims to sensitize the subjects by means of two arguments: the contact with nature followed by dialog and the contact with nature in the light of philosophical principles. All the process was guided by Phenomenology and the interpretation of the experiences was possible with the help of Hermeneutics. The present work was based on the following research question: Does the recalling of the students life stories connected with biophilia (contact with nature) make any change in their being and acting in the world? The awareness of the factors that cause the conflicting relationships was achieved not only by the researcher but also by the students who took part in the research. The importance of this research lies in its revealing of the several conflicting situations found in the educational environment and of the intervening measures which may be taken to minimize them